RESIKO DAN PERLINDUNGAN HUKUM BAGI PEKERJA ANAK BERDASARKAN UNDANG-UNDANG NO. 13 TAHUN 2003 TENTANG KETENAGAKERJAAN JO. UNDANG-UNDANG NO. 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Ayuna Putri, Sherly; Singadimedja, Holyness N (VYAVAHARA DUTA, 2018)
Every child has the right to survival, growth and development and is entitled to protection from violence and discrimination as provided for in the 1945 Constitution of the State of the Republic of Indonesia. A child is a person who is not yet 18 years old, including a child who still in the womb. The legal issues raised in this study are: what is the risk for underage child labor according to positive laws in Indonesia?; and how children?s rights and legal protections for child labor are based on Law no. 13 of 2003 on Manpower and Law no. 35 Year 2014 on Child Protection? This research is normative juridical research with analytical descriptive and qualitative descriptive research specification. This is a Library Research by using secondary data. Some factors that can prevent children to work are: social institutions (custom rules in hereditary societies); weak business that is impossible to work in it or because of the high level of welfare; public view; Education related to the exam season, scholarships, school rules and working hours coinciding with school hours; and the attitude and prohibition of work from parents. Child labor reduction program and children?s opinion are crucial to local potential as a resource of action and community?s responsibility to participate. The program should involve all institutions related to the causal factors and carried out with good coordination because the problems of child labor and its emerging protection are interrelated and strengthen each other.